EFFECT OF EXTENDERS AND TRANSPORTATION SYSTEMS IN FROZEN SEMEN ANALYZED BY COMPUTATIONAL METHOD HOME IN NELORE BULLS (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The objective was to evaluate diluents and transport systems on semen quality frozen by CASA in Nellore bulls. Five semen collections of six bulls, diluted with the TRIS and BotuBOV®, were transported out on two types of BotuBOX® and BotuFLEX® systems; frozen and analyzed by CASA. TM was higher (p